Gas‐Phase Alkali Metal‐Assisted MOCVD Growth of 2D Transition Metal Dichalcogenides for Large‐Scale Precise Nucleation Control. Issue 20 (21st April 2022) - Kim, Tae Soo; Dhakal, Krishna P.; Park, Eunpyo; Noh, Gichang; Chai, Hyun‐Jun; Kim, Youngbum; Oh, Saeyoung; Kang, Minsoo; Park, Jeongwon; Kim, Jaewoo; Kim, Suhyun; Jeong, Hu Young; et al.
Abstract: Advances in large‐area and high‐quality 2D transition metal dichalcogenides (TMDCs) growth are essential for semiconductor applications. Here, the gas‐phase alkali metal‐assisted metal‐organic chemical vapor deposition (GAA‐MOCVD) of 2D TMDCs is reported. It is determined that sodium propionate (SP) is an ideal gas‐phase alkali‐metal additive for nucleation control in the MOCVD of 2D TMDCs. The grain size of MoS2 in the GAA‐MOCVD process is larger than that in the conventional MOCVD process. This method can be applied to the growth of various TMDCs (MoS2, MoSe2, WSe2, and WSe2 ) and the generation of large‐scale continuous films. Furthermore, the growth behaviors of MoS2 under different SP and oxygen injection time conditions are systematically investigated to determine the effects of SP and oxygen on nucleation control in the GAA‐MOCVD process. It is found that the combination of SP and oxygen increases the grain size and nucleation suppression of MoS2 . Thus, the GAA‐MOCVD with a precise and controllable supply of a gas‐phase alkali metal and oxygen allows achievement of optimum growth conditions that maximizes the grain size of MoS2 . It is expected that GAA‐MOCVD can provide a way for batch fabrication of large‐scale atomically thin electronic devices based on 2D semiconductors. Abstract : The gas‐phase alkali metal‐assisted MOCVD (GAA‐MOCVD) for 2D semiconductors with advanced nucleation control realizes the grain size enhancement and generation of MoS2 continuous films with large‐scale spatial homogeneity. In addition, this method enables the grain size enhancement to be maximized as a result of precise and controllable feeding of gas‐phase precursors.